Preoperative Stimulation of Erythropoiesis in Patients with Anemia - V. I. Zagrekov; A. V. Taranyuk; G. A. Maksimov; I. Yu. Yezhov (Общая реаниматология, 2010)
Objective: to comparatively study different postoperative analgesia modes in patients undergoing reconstructive interventions into the abdominal aorta. Subjects and methods. The impact of analgesia on the course of the early postoperative period was comparatively studied in 98 patients. According to the mode of postoperative analgesia, the patients were divided into 3 groups: 1) 35 patients received traditional analgesia with narcotic analgesics (promedol, morphine i.m.); 2) 32 patients had prolonged epidural infusion of 0.2% ropivocaine solution with fractional epidural administration of fentanyl 0.1 mg twice daily; 3) 31 patients were given a combination of epidural naropine and fentanyl with parenteral ketorolac 90 mg/day and paracetamol 3 g/day. The magnitude of pain syndrome was analyzed using the visual analogue scale. The parameters of central hemodynamics (CHD) were estimated applying thoracic tetrapolar rheocardiography. Autonomic homeostatic changes were studied from the cardiac rhythm variability by computer rhythmocardiography. Results. The least magnitude of pain syndrome, the eutonic type of autonomic regulation of the cardiovascular system, and the highest cardiac index values were recorded in Group 3. Conclusion. The use of mul-timodal postoperative analgesia ensures valid analgesia with the stable parameters of CHD and autonomic homeostasis. Key words: analgesia, epidural infusion, visual analogue scale, central hemodynamics, cardiac rhythm variability.